"Allama Sahabbir Ahmed Uthmani’s Efforts for Islamization in Pakistan " - Dr. Abdul Qadir Buzdar; Dr. Khalil Ahmed; Dr. Turab-ul-Hassan Sargana (الإيضاح, 2016)
Allama Shabbir Ahmed Uthmani was one of the prominent religious personalities who made efforts for islamization in Pakistan. So far as the major slogan in 1946 elections were to have a separate homeland of the Muslims where they may be able to live according to the Islamic values. It means Islam was the real power behind the struggle for Pakistan in 1947.After the making of Pakistan a religious scholar Allama Shabbir Ahmed Uthmani presented his services for isalmization in Pakistan as in this respect he had a unique role for the enforcement of Islamic system in Pakistan. Maulana Shabbir Ahmed Uthmani wants to see the constitution of Pakistan to be the leading document towards religious state. In this respect Allama Shabbir Ahmed Uthmani made critical efforts for designing the constitution of Pakistan which was finally approved by the Constitutional Assembly of Pakistan.